The removal of Methylene Blue and Remazol Brilliant Blue R dyes by using orange peel and spent tea leaves - Mat Lazim, Zainab (Penerbit UTM Press, 2015)
This study explored the low-cost adsorbent of orange peel and spent tea leave for Methylene Blue (MB) and Remazol Brilliant Blue R (RBBR) dyes removal from aqueous solutions. The removal rate and adsorption capacity on the adsorption of dyes were investigated using the batch adsorption study. The present study indicates that the MB was easier to remove by both orange peel and spent tea leave compared to RBBR with percentage removal of 95.72 % and 99.02 % respectively. The effects of morphology, functional groups, and surface area of adsorbents were investigated by using FESEM, FTIR, and BET. The result proved that orange peel and spent tea leave were promising material as an alternative adsorbent for the removal of MB from aqueous solution.